(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In modern society, university graduates, especially pedagogical ones, are required to have various abilities: creative, communicative, project-based, and the ability to self-learn throughout their lives. Project activities serve as a means of developing relevant professional competencies. ¬This article examines the ideology of the competency-based approach, implemented in the educational space of a pedagogical university with the help of project-based pedagogical technology, and describes the essence of the professional competencies of pedagogical students.